A Simple Method for Determination of Protodioscin in Tribulus Terrestris L. and Pharmaceuticals by High-Performance Liquid Chromatography Using Diode-Array Detection - Maja Shishovska; Zorica Arsova-Sarafinovska; Shaban Memeti (Journal of Chemical Engineering Research Updates, 2015)
The Tribulus terrestris L. (Zygophyllaceae) is a known medical plant used in traditional and folk medicine worldwide. The steroid saponine protodioscin, an active component found in this plant, serves as a marker for quality control of plant raw materials. In this study, we developed a simple and selective method for determination of protodioscin using convenient High-Performance Liquid Chromatographic (HPLC) laboratory equipment. The detection was performed by Diode-Array Detector (DAD). The proposed method was fully validated and according to the validation results, it was accurate and precise. It was proven to be linear over a protodioscin concentration range of 10,9 to 544.9 µg/mL. The low values of limit of detection (LOD) and limit of quantitation (LOQ) demonstrated adequate sensitivity (16.0 µg and 48.6 µg protodioscin per g plant material, respectively). The proposed method was successfully applied for quality control of a raw plant material intended for use in pharmaceutical industry, as well as for determination of protodioscin in a commercially available pharmaceutical formulation. The positive identification of protodioscin in analyzed samples was done by comparison of retention times of chromatographic peaks and their UV spectra. The content of protodioscin in analyzed samples was: 0.65 – 0.73 % in a raw plant material, and 0.38 % in tablets, respectively.